Barriers and Facilitators in Perioperative Antibiotic Prophylaxis: A Mixed-Methods Study in a Small Island Setting - Liza A. M. van Mun; Sabien J. E. Bosman; Jessica de Vocht; Jaclyn de Kort; Jeroen Schouten (MDPI AG, 2021)
Few studies have addressed antibiotic guideline adherence in small island settings, such as Aruba. This study aimed to evaluate the appropriateness of perioperative antibiotic prophylaxis (PAP) and identify barriers for PAP guideline adherence. A mixed-methods study was carried out at the operating theatre (OT) in the Dr. Horacio E. Oduber Hospital (HOH) in Aruba. First, a prospective audit was performed on the appropriateness of guideline-derived quality indicators (QIs). Then, interviews based on the Flottorp framework were conducted to identify barriers for guideline adherence. Finally, a survey was distributed to verify the outcomes of the interviews. The appropriateness of QIs was measured: correct indication (50.6%); antimicrobial agent (30.8%); dose (94.4%); timing (55.0%); route of administration (100%); duration (89.5%); and redosing (95.7%). The overall appropriateness was 34.9%. The main barriers discovered were poor knowledge about PAP and the guidelines and professional interactions regarding PAP, specifically poor communication and lack of clarity about responsibilities regarding PAP. This study was the first to evaluate the appropriateness and to identify barriers for PAP guideline adherence in a small island hospital. The overall appropriateness of PAP was poor with just 34.9%. Future interventions should be focused on communication, education and awareness of the possibility to consult an ID physician or microbiologist.